Pengembangan snack bar berbasis pangan lokal: analisis gizi dan optimasi formulasi - Indah Purnama Sari; Ditia Fitri Arinda; Windi Indah Fajar Ningsih (Poltekkes Kemenkes Aceh, 2025)
Background: The development of nutritious snack bars is expected to provide a viable solution for offering popular snacks that meet the nutritional needs of adolescents. Therefore, the development of locally sourced snack bars like Puanchi Bar, which substitutes fish glue flour, becomes a promising solution to support government nutrition programs.Objectives: This study aims to analyze the nutritional content and formulation accuracy of three snack bar formulations. Methods: The research design used in this study is a laboratory experimental design with proximate tests, including analysis of protein content, fat content, moisture content, ash content, and carbohydrate content. The study was conducted from May to November 2023 in three laboratories, using three snack bar formulations: F3, F6, and F9. This research utilizes both secondary and primary data. Secondary data was obtained from previous studies, while primary data was obtained through laboratory testing. The data were analyzed using ANOVA, Duncan, and Kruskal-Wallis testsResults: The results showed that formulation F9 has the highest overall nutritional content, particularly in protein and minerals, with an average protein content of 5,10%, ash content of 2,48%, and moisture content of 5,66%, which are higher than F3 and F6. Meanwhile, formulations F3 and F6 excel in carbohydrate and fat content, with F3 and F6 having carbohydrate levels of 64,52% and 64,73%, respectively. The fat content of F3 and F6 is 27,8% and 24,5%, respectively. Formulation F9 is considered more suitable for fulfilling protein and mineral needs, but attention must be given to its moisture content, which could affect shelf life. On the other hand, F3 and F6 are superior in taste and energy but require adjustments to their fat content to maintain a balanced nutritional profile.Conclusion: Formulation F9 is more suitable for meeting protein and mineral needs, while F3 and F6 are better for providing energy and preferred taste. Each formulation has different potential depending on specific nutritional requirements.